Design and optimization of hybrid solar-hydrogen generation system using TRNSYS. (11th June 2020) - Saleem, Muhammad Shoaib; Abas, Naeem; Kalair, Ali Raza; Rauf, Shoaib; Haider, Aun; Tahir, Muhammad Suleman; Sagir, Muhammad
Abstract: Solar thermal systems are an efficient utilization of solar energy for hot water and space heating at domestic level. A Solar Water Heater (SWH) incorporating an Evacuated Glass Tube Collector (EGTC) is simulated using TRNSYS software. Efficiency parameters are pointed, and a parametric optimization method is adopted to design the system with maximum conceivable efficiency. In the first part, the selection of refrigerant for heat transportation in SWH loop is presented. A set of 15 working fluids are chosen, and their chemical properties are computed using NIST standard software (REFPROP). The selected working fluids are tested in the system under study and plots for energy gain and temperature are plotted using TRNSYS. Results showed that ammonia (NH3 ) having specific heat 4.6kJ/kg-K and fluid thermal conductivity 2.12 kJ/hr-m supplies peak energy gain of 7500 kJ/h in winter and 8900 kJ/h in summer season along 120 °C temperature rise. On the other hand, R-123 having specific heat 0.65kJ/kg-K and fluid thermal conductivity 0.0293kJ/hr-m showed inferior performance during the simulation. A solar-hydrogen co-generation system is also designed and simulated under low solar insolation and warm climate regions to study annual hydrogen produced by the hybrid system. System comprises main components: a PV array, an electrolyzer, a fuel cell, a battery, a hydrogen storage unit and a controller in the complete loop. Results of Hydrogen cogeneration system provide 7.8% efficiency in the cold climate of Fargo North Dakota state due to lower solar insolation. While hot climate condition of Lahore weather provides efficiency of 11.8% which satisfy the statistics found in literature. Highlights: Simulation based performance analysis has been carried out using TRNSYS® software. Proposed model is tested for 15 fluids for hybrid solar hydrogen production. TRNSYS shows an excellent choice for solar based hydrogen simulation.